A Study on Employees Work Motivation and its Effect on their Performance and Business Productivity - Al Jasmi, Samira (2012)
This research paper investigates the relationship between employee work motivation and their performance in the workplace and business productivity. It examines the main and common motivation theories and different approaches to motivate employees. The main aim is to find a correlation between employees work motivation and their performance and the performance effect on business productivity. Concerns were found with the employees motivation and performance and the relationship between them clearly defined in the literature review and lately have been discussed in the findings and discussions based on the data analysis done. In order to collect data, interview has been done for people from seven different operational as well technical divisions in the organization. Five people have been chosen from each division. A phone call for the employee about the interview and if he/she is willing to go for it was there, then a meeting request has been sent to every employee for interview for maximum one hour. The total numbers of interview conducted are 35.